Growth Mindset Sebagai Strategi Peningkatan Prestasi Akademik Siswa SMA - Nosy Restia; Surawan, Surawan (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study aims to examine the relationship between growth mindset and students' academic achievement at SMA. Growth mindset, introduced by Carol Dweck, refers to the belief that intellectual abilities can develop through effort and continuous learning. Employing a quantitative approach and a descriptive correlational design, the study involved 30 students selected through purposive sampling. Data were collected using a structured questionnaire to assess growth mindset, and report card scores as indicators of academic achievement. The instruments were tested for validity and reliability prior to data collection. Normality tests indicated that the data were normally distributed, allowing the use of parametric tests. Pearson correlation analysis revealed a positive and significant relationship between growth mindset and academic achievement (r = 0.512, p = 0.004). Furthermore, a simple linear regression showed that growth mindset contributed 26.2% to the variance in academic achievement. This research concludes that growth mindset can be an effective strategy to enhance students’ academic outcomes and recommends schools to cultivate a learning environment that fosters a growth-oriented mindset.